2007
DOI: 10.1097/blo.0b013e318137968c
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Fractures in Revision Hip Surgeries with Impacted Bone Allograft

Abstract: Impacted allograft bone in hip revision arthroplasty is a biologic reconstruction method that restores bone loss. Periprosthetic femoral fracture is one of the most frequent complications. However, the incidence, types of fracture, time of occurrence, predisposing factors, and whether and how complication affects the reconstruction are unknown. We analyzed 285 femoral revisions performed with this technique. Fractures occurred in 64 patients (22.4%). Fifty-nine of these 64 incidents (92%) occurred during surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
0
21
1
2
Order By: Relevance
“…In contrast, types of complications were different from those after revision in older patients. The fracture rate (14%) in our patients was lower than the rate after THA revision in older patients (16% reported by Park et al [27], 22% reported by Farfalli et al [14], and 30% reported by Meek et al [22]). The dislocation rate (15%) for our patients was higher than usually observed after revision THAs (5% reported by Park et al [27], 8% reported by Kinkel et al [20], and 9% reported by Ornstein et al [26]).…”
Section: Discussioncontrasting
confidence: 66%
“…In contrast, types of complications were different from those after revision in older patients. The fracture rate (14%) in our patients was lower than the rate after THA revision in older patients (16% reported by Park et al [27], 22% reported by Farfalli et al [14], and 30% reported by Meek et al [22]). The dislocation rate (15%) for our patients was higher than usually observed after revision THAs (5% reported by Park et al [27], 8% reported by Kinkel et al [20], and 9% reported by Ornstein et al [26]).…”
Section: Discussioncontrasting
confidence: 66%
“…However, the strengths of our study must also be highlighted: the evaluation of intra-operative fractures in a large sample, and among patients with cemented prostheses and revision surgeries with impacted bone graft, which knowingly is a risk factor for periprosthetic fractures, especially when a short implant is used [22][23][24].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, once antibiotic is depleted, the graft is again susceptible to bacterial colonization. Therefore, although use of allograft has yielded excellent results, its use in cases of infection has been controversial as a result of the possible increased risk of reinfection [8,9,18].…”
Section: Discussionmentioning
confidence: 99%